2017
DOI: 10.4014/jmb.1611.11056
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Biofilm, a Programmed Bacterial Life for Fitness

Abstract: A biofilm is a community of microbes that typically inhabit on surfaces and are encased in an extracellular matrix. Biofilms display very dissimilar characteristics to their planktonic counterparts. Biofilms are ubiquitous in the environment and influence our lives tremendously in both positive and negative ways. Pseudomonas aeruginosa is a bacterium known to produce robust biofilms. P. aeruginosa biofilms cause severe problems in immunocompromised patients, including those with cystic fibrosis or wound infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
111
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(114 citation statements)
references
References 115 publications
(193 reference statements)
1
111
0
2
Order By: Relevance
“…The data presented here suggest that the intraisolate variability of these factors alters OMV production, which may play an important part in bacterial fitness in natural environments and within the host. P. aeruginosa is known to grow in a biofilm both in the environment and in infectious niches, such as the airways of patients with cystic fibrosis (39,40). High levels of extracellular DNA (eDNA) production have been linked to biofilm development and propagation (41,42).…”
Section: Figmentioning
confidence: 99%
“…The data presented here suggest that the intraisolate variability of these factors alters OMV production, which may play an important part in bacterial fitness in natural environments and within the host. P. aeruginosa is known to grow in a biofilm both in the environment and in infectious niches, such as the airways of patients with cystic fibrosis (39,40). High levels of extracellular DNA (eDNA) production have been linked to biofilm development and propagation (41,42).…”
Section: Figmentioning
confidence: 99%
“…The involvement of P. aeruginosa QS systems in biofilm life cycle was firstly reported by Davis et al as they demonstrated that lasI mutants form only flat and undifferentiated biofilm structures [126]. Therefore, Las system is mainly in use for mature biofilm development [127]. Other investigators reported that rhlI gene is involved in the formation of a mushroom-like structures and are also crucial in the dispersal stage controlling the production of rhamnolipids [128,129].…”
Section: Qs Systems Of P Aeruginosamentioning
confidence: 94%
“…The biofilm lifecycle is composed of several commonly reported steps 1,[6][7][8] . Initially, planktonic bacteria propel themselves to a proximal surface, followed by an irreversible attachment to the surface.…”
Section: Mainmentioning
confidence: 99%
“…We decided to introduce modifications mainly in the D3 domain of flagellin, facing outwards in the cylindrical structure of flagellum, thus minimizing possible interference with filament assembly 32 . We modulated the P. aeruginosa flagellum that is composed of 41 subunits (based on PDB accession number 5wk5) with (1) incorporated at flagellin's th position (Fig. 2a).…”
Section: Uaasmentioning
confidence: 99%